Problems of the Formation and Development of Diaspora Business in the Regions of Western Siberia - Simonov, Sergey Gennadievich; Khamatkhanova, Makka Alaudinovna; Lysenko, Igor Vyacheslavovich (International Journal of Economics and Financial Issues, 2015)
Using the example of the Tyumen region, the experience of inter-ethnic interaction, formation and development of diaspora business is summed up. The results of the social research, conducted in 2013-2015 within the framework of the scientific community “The Social Responsibility of Business” on the basis of the Tyumen State Oil and Gas University are presented. The representatives of the regional public service and ethnic business took part in the research. Keywords: ethnos, ethnic community, diaspora, inter-ethnic interaction, diaspora business. JEL Classifications: M38, M21, R11, R58